Analysis of Sosopan Hot Spring Tourism Object Development to Attract Tourists in the West Pasaman Simpang Lolo Area (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Sosopan hot spring tourism is one of the tourist destinations located in the Nagari Rabi Jonggor area, Gunung Tuleh sub-district, West Pasaman Regency, this tour is one of the tours that has not been exposed or there are still many people who do not know about these tourist attractions. Even though the hot springs are very interesting to visit and there are many benefits for visitors to these tours, one of which is that visitors can take treatment in these hot waters and also at these tourist sites offer the beauty of the natural panorama of West Pasaman Regency. So that researchers are very interested in developing Sosopan Hot Spring tourism in Nagari Rabi Jonggor, Gunung Tuleh sub-district, West Pasaman Regency. There are several obstacles in developing hot spring tourism in Nagari Rabi Jonggor, namely as follows; Inadequate accessibility, inadequate facilities, poor security, poor hygiene and poor service. By conducting an analysis using the interpretive structural modeling (ISM) model, there are five sub-elements that have high driver power and low dependency, namely; E1 (inadequate accessibility), E2 (poor facilities), E3 (poor security), E4 (poor cleanliness), E7 (poor service). Constraints in the development of Rabi Jonggor Nagari hot spring tourism, Gunung Tuleh sub-district, West Pasaman Regency, there are five levels and priority directions in overcoming obstacles, namely accessibility and facilities.